1999
DOI: 10.1002/(sici)1099-0844(199909)17:3<207::aid-cbf830>3.0.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

The levels of some antioxidant vitamins, glutathione peroxidase and lipoperoxidase during the anaesthesia of dogs

Abstract: The aim of this investigation was to determine serum levels of vitamin A, E, beta carotene, glutathione peroxidase (GSHPx), lipid peroxidation (MDA) and biochemical and haematological parameters during enflurane anaesthetised dogs. Ten kangal dogs were used and all animals were anaesthetised with enflurane for two hours and blood samples were taken before and 30, 120 minutes, 24 hours and 7 days during the anaesthesia. Vitamin E and beta carotene content were significantly (p<0.05 and p<0.01) higher before ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0
4

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 17 publications
1
23
0
4
Order By: Relevance
“…Similar data were also reported in dogs anaesthetized by xylazine and ketamine, however no duration of surgery was given (Gunay et al 2011). MDA increased 30 minutes after but did not change 2 and 24 h after exposure of enflurane anaesthesia for 2 hours in dogs, whereas GSH concentration displayed no significant difference (Naziroglu and Gunay 1999). Moreover, Alva et al (2006) reported that one hour exposure of xylazine and ketamine or pentobarbital-induced anaesthesia which was given every 30 minutes for maintenance of anaesthesia did not alter MDA levels at 15 and 60 minutes, while GSH decreased.…”
Section: Discussionmentioning
confidence: 99%
“…Similar data were also reported in dogs anaesthetized by xylazine and ketamine, however no duration of surgery was given (Gunay et al 2011). MDA increased 30 minutes after but did not change 2 and 24 h after exposure of enflurane anaesthesia for 2 hours in dogs, whereas GSH concentration displayed no significant difference (Naziroglu and Gunay 1999). Moreover, Alva et al (2006) reported that one hour exposure of xylazine and ketamine or pentobarbital-induced anaesthesia which was given every 30 minutes for maintenance of anaesthesia did not alter MDA levels at 15 and 60 minutes, while GSH decreased.…”
Section: Discussionmentioning
confidence: 99%
“…Anestezi esnasında; hipoksinin, antioksidan vitamin ve ya enzim düzeyinin azalmasının hücresel seviyede oksidan/antioksidan dengesinin bozulmasına yol açabileceği düşünülmektedir. 12 Desfluran hepatotoksisitesi için özgül bir radikal bulunmamasına rağmen, antioksidan vitamin ya da enzim seviyelerinde değişikliğe neden olan dolaylı bir etki ile hepatotoksisitenin geliştiği gösterilmiştir. 12,13 Ça-lışmamızda oksidatif stres değerlendirilirken, antioksidan gösterge olarak, büyük oranda karaciğerde sentez edilip salgılanan PON1 temel alın-mıştır.…”
Section: Discussionunclassified
“…12 Desfluran hepatotoksisitesi için özgül bir radikal bulunmamasına rağmen, antioksidan vitamin ya da enzim seviyelerinde değişikliğe neden olan dolaylı bir etki ile hepatotoksisitenin geliştiği gösterilmiştir. 12,13 Ça-lışmamızda oksidatif stres değerlendirilirken, antioksidan gösterge olarak, büyük oranda karaciğerde sentez edilip salgılanan PON1 temel alın-mıştır. 30,31 Primer olarak organafosfat detoksifikasyonunda rol alan PON1, doğal antioksidan bir enzim olarak kabul edilmektedir.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Previous studies in animals have suggested that exposure to volatile anesthetics can induce oxidative stress (Nazirolu and Gunay, 1999;Nazirolu and Cay, 2001). Our body is equipped with ample cache of defenses against reactive oxygen species (ROS).…”
Section: Introductionmentioning
confidence: 99%